2014
DOI: 10.1007/10_2014_269
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids in Human and Animal Nutrition

Abstract: Amino acids are key components of human and animal nutrition, both as part of a protein-containing diet, and as supplemented individual products. In the last 10 years there has been a marked move away from the extraction of amino acids from natural products, which has been replaced by efficient fermentation processes using nonanimal carbon sources. Today several amino acids are produced in fermentation plants with capacities of more than 100,000 tonnes to serve the requirements of animal feed and human nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 80 publications
1
32
0
Order By: Relevance
“…For example, they found that L-glutamine regulates small intestinal bacterial metabolism of arginine, serine, and aspartate, and reduced the catabolism of essential and non-essential amino acids. This is especially relevant given the fact that modern food processing has a dramatic effect on the relative concentrations of amino acids present in commonly consumed processed foods and recent evidence for important physiological roles for both essential (e.g., tryptophan) and non-essential amino acids in mammalian nutrition [ 49 51 ].…”
Section: Proteinsmentioning
confidence: 99%
“…For example, they found that L-glutamine regulates small intestinal bacterial metabolism of arginine, serine, and aspartate, and reduced the catabolism of essential and non-essential amino acids. This is especially relevant given the fact that modern food processing has a dramatic effect on the relative concentrations of amino acids present in commonly consumed processed foods and recent evidence for important physiological roles for both essential (e.g., tryptophan) and non-essential amino acids in mammalian nutrition [ 49 51 ].…”
Section: Proteinsmentioning
confidence: 99%
“…As one of the three branched‐chain amino acids (BCAAs), l ‐valine is an essential nutrient for humans and animals. It is used in infusion solutions and human dietary supplements (Karau & Grayson, ), commercial feed in the swine and poultry industries (Oldiges, Eikmanns, & Blombach, ), and as a precursor for herbicide and antibiotic synthesis (Oldiges et al, ). Traditional extraction of l ‐valine, and most other amino acids, from protein hydrolysate has been replaced by microbial production and/or enzymatic synthesis (Xie, Liang, Huang, & Xu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lys deficiency is also the major cause of the osteoporosis in humans [ 18 ]. Stress-induced anxiety in mice was reportedly caused by the lack of Lys in their daily diets [ 19 , 20 ]. A diet deficient in Met and Lys intake can reduce biological value of plant-based nutrition to 50-70%, compared to a balanced diet with high abundance of essential amino acids [ 21 ].…”
Section: Nutritional Roles Of Essential Amino Acidsmentioning
confidence: 99%